Pengembangan Metode Pembelajaran Dengan Konsep Sintesis Sains dan al-Quran (SSQ) - Sudarmanto, Eko; Amarullah, Ahmad; Saleh, Hairul; Yusuf, Siti Rabiah (Institut Agama Islam Sahid (INAIS) Bogor, 2023)
This research aims to develop a learning method using the Science and Quran Synthesis (SSQ) approach. The study utilizes a literature review approach, applying content analysis as a type of conceptual qualitative study. The research findings indicate that the Science and Quran Synthesis approach is a new concept in teaching methods that is more contextual and relevant. It aims to help learners gain a deeper understanding of scientific concepts and the ability to integrate relevant Quranic verses with contemporary scientific topics.